2020
DOI: 10.1080/20008198.2019.1708618
|View full text |Cite
|
Sign up to set email alerts
|

Females have more complex patterns of childhood adversity: implications for mental, social, and emotional outcomes in adulthood

Abstract: Background: Adverse childhood experiences (ACEs) have been identified as an important public health problem with serious implications. Less well understood is how distinct configurations of childhood adversities carry differential risks for mental health, emotional, and social outcomes later in life. Objective: To determine if distinct profiles of childhood adversities exist for males and females and to examine if unique associations exist between the resultant latent profiles of childhood adversities and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 68 publications
(72 reference statements)
14
62
2
Order By: Relevance
“…Analysis revealed gender differences regarding trauma exposure, with girls reporting significantly higher rates of sexual abuse, sexual assault and sudden/violent death of a close person (e.g. Haahr-Pedersen et al, 2020 ). Subsequent analysis evidenced gender differences regarding CPTSD symptomatology, with girls exhibiting significantly higher rates of PTSD and DSO symptoms, as has been shown in studies in adults (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis revealed gender differences regarding trauma exposure, with girls reporting significantly higher rates of sexual abuse, sexual assault and sudden/violent death of a close person (e.g. Haahr-Pedersen et al, 2020 ). Subsequent analysis evidenced gender differences regarding CPTSD symptomatology, with girls exhibiting significantly higher rates of PTSD and DSO symptoms, as has been shown in studies in adults (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…No country is immune to the problem of violence, including domestic violence, the consequences of which can be devastating [52]. There are gender differences in sexual abuse, physical abuse and household violence in childhood and female are vulnerable groups [53], which reminds us to pay more attention to the mental health of women.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, demonstrating that disaggregation by sex is important. In further support of this, one study that assessed gendered profiles of adversity concluded that there are separate and distinct patterns of childhood adversities, with females experiencing more complex and varied patterns [29].…”
Section: Implications Of Findingsmentioning
confidence: 94%
“…The objectives of this study are therefore to (a) examine the associations between ACEs and adult human capital, and (b) explore how the measurement of ACEs may vary in relation to these human capital outcomes. Prior research, including studies using this cohort, have highlighted sex differences in the prevalence of ACEs and their associations with outcomes [17,24,[27][28][29][30]. The patterning of ACEs and their links to human capital outcomes will be disaggregated by sex throughout this analysis.…”
Section: Introductionmentioning
confidence: 99%